Comparison of the Inhibitory Effects of the TXA2 Receptor Antagonist, Vapiprost, and Other Antiplatelet Drugs on Arterial Thrombosis in Rats: Possible Role of TXA2 - Takiguchi, Yoshiharu; Wada, Kouichirou; Nakashima, Mitsuyoshi (Thrombosis and Haemostasis, 1992)
The antithrombotic effect of the thromboxane A2 receptor antagonist, vapiprost, was compared with those of other antiplatelet drugs using an arterial thrombosis model which utilized photochemical reaction in the rat femoral artery. Vapiprost prolonged the time required to occlude the artery with thrombus and inhibited collagen-induced rat platelet aggregation in whole blood ex vivo, in a dose-dependent manner. The potency ranking of antithrombotic effect was vapiprost > ketanserin (serotonin 5-HT2 receptor antagonist) >> ticlopidine (inhibitor of ADP-induced platelet aggregation) = dipyridamole (adenosine uptake inhibitor) >aspirin (cyclooxygenase inhibitor). On the other hand, the ranking of antiplatelet effect was ticlopidine ≥vapiprost ≥aspirin. Ketanserin and dipyridamole were ineffective. Relative to their antiplatelet effect, vapiprost and ketanserin had powerful antithrombotic effects. It is possible that the potent antithrombotic effects of vapiprost and ketanserin in vivo reflect the ability of these drugs to inhibit mediator-induced vascular contractions in addition to platelet aggregation. The results of the present study also suggest that TXA2 may play an important role in thrombogenesis in rats.